FACTORS AFFECTING THE DECISION TO CHOOSE THE SERVICE OF THE GREAT HOUSE POOL VILLA, KHAO CHI CHAN, PATTAYA CHONBURI PROVINCE - Leekool, Supannapak (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to 1) study the factors affecting the decision to choose to use the service of The Great House Pool Villa Khao Chi Chan Pattaya, Chonburi Province and 2) to compare the level of factors affecting the decision to use The Great House Pool Villa Khao Chi Chan Pattaya, Chonburi Province. It is a survey research using a questionnaire with a sample of 99 people. The data were analyzed using statistics, including percentage, mean, standard deviation, testing the mean with Independent Samples t-test and One way ANOVA. The difference between the mean of the 2 sample groups was compared using Independent Samples t-test and comparing the difference between the mean of more than 2 sample groups using One-Way ANOVA. The research results found that 1) The factors affecting the decision to use the service of The Great House Pool Villa Khao Chi Chan Pattaya, Chonburi Province, overall, had high opinions. When considering each aspect with high opinions in 5 aspects, namely personnel, physical characteristics, efficiency and quality, and marketing promotion Service process aspect, respectively, and each aspect with moderate level of opinion in 3 aspects: product aspect, distribution aspect, price aspect, respectively, and 2) Hypothesis testing found that the sample groups with different gender, age, marital status, education level, occupation and income had no different opinions on the decision to use the service overall. For the suggestion in this research, the company's executives should have a policy to promote training for employees to be neat, polite, friendly and honest because these are factors that affect the decision to use the service. The Great House Pool Villa Khao Chi Chan Pattaya, Chonburi Province, overall, is at a high level and has the most influence on the decision to use the service.